Mining the nucleus accumbens proteome for novel targets of alcohol self-administration in male C57BL/6J mice - Faccidomo, Sara (Psychopharmacology (Berl), 2018)
RATIONALE: There is a clear need for discovery of effective medications to treat behavioral pathologies associated with alcohol addiction, such as chronic drinking. OBJECTIVE: The goal of this preclinical study was to assess effects of chronic alcohol drinking on the nucleus accumbens (NAcb) proteome to identify and validate novel targets for medications development. MATERIALS AND METHODS: Two-dimensional difference in-gel electrophoresis (2D-DIGE) with matrix assisted laser desorption ionization tandem time-of-flight (MALDI-TOF/TOF) was used to assess effects of chronic voluntary home-cage (24-h access) alcohol drinking on the NAcb proteome of C57BL/6J mice. To extend these findings to a model of alcohol self-administration and reinforcement, we investigated potential regulation of the positive reinforcing effects of alcohol by the target protein glutathione S-transferase Pi 1 (GSTP1) using a pharmacological inhibition strategy in mice trained to self-administer alcohol or sucrose. RESULTS: Expression of 52 unique proteins in the NAcb was changed by chronic alcohol drinking relative to water control (23 upregulated, 29 downregulated). Ingenuity Pathway Analysis showed that alcohol drinking altered an array of protein networks associated with neurological and psychological disorders, molecular and cellular functions, and physiological systems and development. DAVID functional annotation analysis identified 9 proteins (SNCA, GSTP1, PRDX3, PPP3R1, EIF5A, PHB, PEBP1/RKIP, GAPDH, AND SOD1) that were significantly overrepresented in a functional cluster that included the Gene Ontology categories “response to alcohol” and “aging.” Immunoblots confirmed changes in Pebp1 (RKIP) and GSTP1 in NAcb with no change in amygdala or frontal cortex, suggesting anatomical specificity. Systemic inhibition of GSTP1 with Ezatiostat (0–30 mg/kg, i.p.) dose-dependently reduced the reinforcing effects of alcohol as measured by operant self-administration, in the absence of motor effects. Sucrose self-administration was also reduced but in a manner associated with nonspecific motor inhibition. CONCLUSIONS: Protein expression profiling identified an array of proteins and networks in the NAcb, including GSTP1, that are novel molecular targets of chronic alcohol drinking. Pharmacological inhibition of GSTP1 significantly reduced the positive reinforcing effects of alcohol, which regulate repetitive use and abuse liability. The observation that this protein was both up-regulated after chronic drinking and that its inhibition could modulate the reinforcing properties of alcohol suggests that it is a key target for alcohol-related pathologies. Proteomic strategies combined with specific preclinical models has potential to identify and validate novel targets of alcohol that may be useful in the medical management of alcohol addiction.